Clarithromycin in post COVID-19 organizing pneumonia - Ayub, Irfan Ismail; Thangaswamy, Dhanasekar; Arshad, Abdul Majeed; Chockalingam, Chandrasekar; Sampath, Lithya Kumari; Balakrishnan, Hariprasad (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
An increasing number of patients are reporting with symptoms secondary to post COVID-19 pulmonary sequelae. Radiological findings in these patients include fibrotic lung disease, interstitial lung abnormalities, ground glass opacities, and organizing pneumonia (OP). Therapeutic options in these patients include steroids and anti-fibrotics. The majority of these patients have received steroid therapy for COVID-19 pneumonia, and may continue to receive it for post COVID-19 pulmonary sequelae, subjecting themselves to steroid related adverse effects. Cryptogenic organizing pneumonia (COP) responds well to steroid therapy. Alternatively, macrolide therapy has been successful in the treatment of both cryptogenic and secondary forms of OP. Compared to steroid therapy, macrolide therapy in COP is well tolerated and associated with fewer adverse events. We report two patients who were diagnosed with post COVID-19 OP and were treated with clarithromycin for three months. We believe that clarithromycin offers a potential therapeutic option in post COVID-19 organizing pneumonia.